A macroergonomic perspective on fatigue and coping in the hospital nurse work system. (May 2016) - Steege, Linsey M.; Dykstra, Jessica G.
Abstract: Occupational fatigue in hospital nurses is associated with increased nurse turnover, and decreased nurse health and patient safety. The goal of this study was to explore the factors contributing to or preventing fatigue, and barriers and facilitators to individual nurse coping in hospital work systems. Interviews were conducted and analyzed using a directed qualitative content analysis approach guided by the Systems Engineering Initiative for Patient Safety (SEIPS) model. Themes related to sources of fatigue within each of the five primary components of the SEIPS work system were identified, along with barriers and facilitators to nurses' experiences and strategies for coping with fatigue. Findings from this study provide guidance on what nurses perceive as contributing to fatigue and factors that are helpful and harmful to coping with fatigue within their work system. Implications for fatigue risk management systems (FRMS) are also discussed, in particular the importance of maintaining nurse autonomy in decision-making when implementing fatigue interventions or countermeasures. Highlights: We explore hospital registered nurses' perceptions of fatigue and coping at work. We apply the SEIPS model to find barriers and facilitators to fatigue and coping. Factors that contribute to or prevent fatigue span work system components. Barriers and facilitators to coping also span all work system components. Fatigue risk management in hospital nursing should apply a macroergonomic approach.